Varennes-sur-Seine (Seine-et-Marne), la Justice : l’ensemble funéraire aristocratique de La Tène finale et les aménagements gallo-romains - Jean-Marc Séguier (Revue Archéologique du Centre de la France)
The La Justice funerary complex at Varennes-sur-Seine (Seine-et-Marne) is located 350 m from the aristocratic settlement of the same name, on the edge of a paleochannel. Partially circumscribed, it covers an area of 3,300 m² and comprises 6 quadrangular monuments of varying shape, 2 ditches, 4 pits, 2 postholes, 1 deposit and 6 piles of furniture. No burials in the strict sense of the term were found, a result of both erosion and the particularities of burial rites. The cremated human remains, which are not very abundant (less than 500 g), and the furniture, which is very abundant (over 192 kg), come principaly from the backfill of monument ditches, other ditches and heaps. The material consists mainly of a large number of amphora remains (over 3,250), almost all of them Dr. 1 Italic, as well as 44 coins, while the ceramics and metal instrumentum are very discreet. The importance of wine in the ritual, the presence of a statere and that of Campanian tableware are consistent with the very high social standing of the occupants of the settlement to which the funerary complex belongs. The structures and furnishings reveal funerary practices that are atypical in the Gallic context, or at least not easy to decipher. However, the data is echoed at several sites in the Île-de-France region that have yielded comparable remains, with funerary rituals appearing to characterize the social elites of the Senon cultural area during the 1st century BC. Abandoned shortly after the conquest, the area was reoccupied from the Flavian period to the 3rd century BC, with elements of a plot of land linked to boundary markers and 4 deposits evoking the rite of enchytrism.